2016
DOI: 10.1038/srep38462
|View full text |Cite
|
Sign up to set email alerts
|

Online flow cytometry reveals microbial dynamics influenced by concurrent natural and operational events in groundwater used for drinking water treatment

Abstract: Detailed measurements of physical, chemical and biological dynamics in groundwater are key to understanding the important processes in place and their influence on water quality – particularly when used for drinking water. Measuring temporal bacterial dynamics at high frequency is challenging due to the limitations in automation of sampling and detection of the conventional, cultivation-based microbial methods. In this study, fully automated online flow cytometry was applied in a groundwater system for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 61 publications
(86 reference statements)
2
60
0
1
Order By: Relevance
“…However, as demonstrated for the GLUC approach, such techniques still demand further research effort and development. Whether the recently emerging online detection systems for TCC enumeration (Besmer et al, 2014(Besmer et al, , 2016Hammes et al, 2008;Hammes, Berger, TABLE 2 Overview on open research questions and future development goals to fully realize the suggested framework for microbial pollution analysis and management Twenty three important research questions and development goals for spring water analysis and management Sampling • What is the best technical approach to support microbiological autosampling to realize hydrological-guided monitoring?…”
Section: Managing the Surface-related Microbial Pollution Componentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as demonstrated for the GLUC approach, such techniques still demand further research effort and development. Whether the recently emerging online detection systems for TCC enumeration (Besmer et al, 2014(Besmer et al, , 2016Hammes et al, 2008;Hammes, Berger, TABLE 2 Overview on open research questions and future development goals to fully realize the suggested framework for microbial pollution analysis and management Twenty three important research questions and development goals for spring water analysis and management Sampling • What is the best technical approach to support microbiological autosampling to realize hydrological-guided monitoring?…”
Section: Managing the Surface-related Microbial Pollution Componentmentioning
confidence: 99%
“…Köster, & Egli, 2010;Van Nevel et al, 2017) also add significant value to this approach has yet to be evaluated. Irrespective of the applicability of currently emerging technologies, the general importance of microbiological online monitoring and automation (e.g., precipitation event-triggered automated sampling) is likely to increase in the near future (Besmer et al, 2016;Højris et al, 2016;Ryzinska-Paier et al, 2014;Stadler et al, 2016). The application of genetic MST markers also holds great promise for future water quality testing.…”
Section: Disinfectionmentioning
confidence: 99%
“…Online FCM with an automatic system for sampling, staining, and cleaning has quickly gained attention and consideration throughout the water sector over the past years to quantify both total and intact bacterial cell counts 22,36,[38][39][40] . The real-time monitoring of bacterial cell numbers through online FCM can be helpful to indicate locations of concern throughout the distribution network.…”
Section: Introductionmentioning
confidence: 99%
“…In this study flow cytometry (FCM) was applied as a rapid method for monitoring general microbiological water quality of distributed water and to evaluate disinfection efficiency (Berney et al 2007;Ramseier et al 2011). The technology has mainly been applied to monitor drinking water systems (Hammes et al 2008 andBesmer et al 2016) with only recent examples evaluating water reuse schemes (Huang et al 2016). The aim of this study was to quantitatively assess the efficiency of bacterial removal in a full-scale MBR blackwater reuse treatment plant in the UK and the change in bacterial numbers during distribution throughout the dedicated distributed network.…”
Section: Introductionmentioning
confidence: 99%